Human perception of combined sound and steering wheel vibrations - Törnqvist, Jonas (My University, 2004)
Various studies have been done on disorders caused by hand-induced vibrations. In the matter of perception of hand-induced vibrations,there is however not very many studies to find in literature. As regards the combined effects of sound and hand-induced vibrations there are even less studies done. This thesis shows that there are statistical significant effects of combined sound and hand-induced vibrations. The purpose of this thesis was to implement realistic sound and vibrations in a truck-rig, placed in the listening test room at Applied Acoustics.Furthermore some combined effects of sound and hand-induced vibrations were to be investigated by a listening test. The limitations on the implementation were that only steering wheel accelerations and sound from a Volvo FH12 at idling were measured and implemented in the rig, i.e. no signals were used from RPM sweeps of the truck. The current setup showed in the thesis, with use of the small shakers,also set some limitations in what accelerations that can be reproduced on the wheel. In the listening test the combinations of three sound stimuli and three vibrational stimuli were tested in order to see what influence their differences in spectral components and levels would have. The sound stimuli were of constant type based on the binaural recordings in driver position in a truck. The vibration stimuli were acceleration with increasing level versus time, of different spectral components. The method for the first part was to find the threshold of sensation and the threshold of acceptance for the increasing and decreasing vibration stimuli. The influences of sound on the thresholds were also to be investigated. In the second part of the listening test the influence of different constant vibrational stimuli on the perceived annoyance of the sound was investigated. The results showed that spectral contents of the vibrations influence both the threshold of sensation and the threshold of acceptance. There were also significant results showing that mismatch in the spectra between sound and vibrations caused both annoyance and a time-delay of the subjects responds. Also that increasing and decreasing vibrations changes the thresholds is shown in the results. The results also showed that the perceived annoyance of the sound differ when the sound was combined with different vibrational stimuli. Finally, the thesis includes some recommendations for further work and also for some improvements that can be made on the rig.
Keywords: Samhällsbyggnadsteknik; Civil Engineering